1979
DOI: 10.1037/0022-3514.37.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Person memory: Personality traits as organizing principles in memory for behaviors.

Abstract: Subjects studied and recalled sentences describing behaviors while performing a laboratory impression-formation task. Recall was high for behaviors that were incongruent with a personality-trait impression for a character, whereas recall was much lower for behaviors that were congruent or neutral with reference to the impression. Set size, the number of congruent and incongruent behaviors attributed to the character, was shown to be a major determinant of this result. The smaller the size of the incongruent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
516
10
19

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 700 publications
(594 citation statements)
references
References 48 publications
49
516
10
19
Order By: Relevance
“…This type of response is a counterexample negative response . This distinction is similar to the distinction made by Hastie and Kumar (1979) between neutral and incongruent trait adjectives . More n.o-example negative (neutral) responses than counterexample negative (incongruent) responses may have occurred in the self condition than i~the~ouse condition.…”
Section: Discussion the Congruent-infonnation Hypothesismentioning
confidence: 59%
See 2 more Smart Citations
“…This type of response is a counterexample negative response . This distinction is similar to the distinction made by Hastie and Kumar (1979) between neutral and incongruent trait adjectives . More n.o-example negative (neutral) responses than counterexample negative (incongruent) responses may have occurred in the self condition than i~the~ouse condition.…”
Section: Discussion the Congruent-infonnation Hypothesismentioning
confidence: 59%
“…that the self-reference effect is independent of the selfdescriptiveness of the target traits. Furthermore, some studies that investigated person stereotypes found that information not congruent with the stereotype is recalled better than is information congruent to it (Hastie & Kumar, 1979;Srull , 1981). One purpose of the experiment described here is to test the congruent-information hypothesis.…”
Section: Subjects and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…When expectations about others are violated, the social impressions of them need to be updated (e.g., Hamilton, Driscoll, & Worth, 1989;Hastie & Kumar, 1979;Reeder & Coovert, 1986). In these situations, individuals usually take longer to integrate information about others that contradicts rather than matches their initial impressions (Reeder & Coovert, 1986).…”
mentioning
confidence: 99%
“…Information that is incongruent with an initial judgment (i.e., a sort of "first impression" of the to-be-evaluated stimuli) is better remembered than congruent information. In a study by Hastie and Kumar (1979), participants were presented with behaviour descriptions about a hypothetical character; later, they were asked to judge her personality. During a following memory test phase, the behaviours that were incongruent with the personality appraisal were better remembered.…”
Section: Could Memory-judgment Associations Be Judgment-driven?mentioning
confidence: 99%